1995
DOI: 10.1002/ijc.2910620311
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo model of intratumoural aromatase using aromatase‐transfected MCF7 human breast cancer cells

Abstract: About two-thirds of human breast carcinomas contain detectable levels of aromatase, the enzyme which converts androgens to oestrogens. Assessment of the importance of this enzyme to breast cancer growth has been hampered by the absence of an adequate model system. We have previously reported that MCF7 human hormone-dependent breast cancer cells transfected with human aromatase cDNA (Arom1 cells) showed a growth response in vitro to exogenous androgens and this effect was blocked by aromatase inhibitors. We rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…These cells, when injected s.c. into immunocompromised mice, form tumors under androstenedione support (20). MCF7 AROM 1 cells convert androstenedione to estradiol providing an intratumoral source of estrogen representative of postmenopausal, hormone-dependent breast cancer.…”
Section: Ptk/zk Reduces Tumor Growth Of Mcf7 and Bt474-derived Human mentioning
confidence: 99%
“…These cells, when injected s.c. into immunocompromised mice, form tumors under androstenedione support (20). MCF7 AROM 1 cells convert androstenedione to estradiol providing an intratumoral source of estrogen representative of postmenopausal, hormone-dependent breast cancer.…”
Section: Ptk/zk Reduces Tumor Growth Of Mcf7 and Bt474-derived Human mentioning
confidence: 99%
“…We present pre-clinical results on novel candidates for clinical development as markers of ER dependent pathway activation and endocrine treatment efficacy. We have performed this study using an animal model that has been shown to predict the behaviour of human ER positive breast cancer when exposed to aromatase inhibitors [22,21]. Extrapolation of our results to human tumours demands great caution given the expected differences between both settings.…”
Section: Discussionmentioning
confidence: 84%
“…Pellets containing 60-day release of 15 mg androstenedione (Innovative Research of America Ò ) were inserted subcutaneously at the same time but in a distant site from tumour cells implant. MCF-7 cells transfected with the aromatase gene (MCF-7 Arom1 cells) [21] were grown to 80% confluence in DMEM culture medium containing 10% FCS, 1% penicillin and streptomicin, 2 mM glutamine, 1 mM sodium pyruvate, 10 lg/ ml insulin and 600 lg/ml G418 to maintain selection for neomycin-resistant cells. Cells were scraped and resuspended in matrigel.…”
Section: Animal Modelmentioning
confidence: 99%
See 2 more Smart Citations